A Curriculum Full of Love in Learning Indonesian Literature: Cultivating A Sense of Love for Culture and National Identity - Junita Irawati; Kholidah Nur; Ali Yusron (Tabasa: Jurnal Bahasa, Sastra Indonesia, dan Pengajarannya, 2026)
The Full of Love Curriculum in Indonesian Literature learning aims to strengthen students' love for culture and national identity through a humanistic approach that prioritizes warm emotional relationships between teachers and students. This study aims to explore the implementation of this curriculum at MAN 1 Mandailing Natal and its impact on students' cultural identity and nationalism. This research uses a qualitative approach with a case study design. Data were collected through observation, in-depth interviews with teachers and students, and analysis of documents related to the curriculum and teaching materials. Researchers analyzed the impact of implementing the Full of Love Curriculum on strengthening students' cultural identity and their pride in Indonesia. The results of the study show that the implementation of the Full of Love Curriculum at MAN 1 Mandailing Natal is effective in fostering a sense of pride in Indonesian culture and strengthening students' national identity. Literary learning that integrates local Mandailing cultural values and Indonesian nationality encourages students to better understand and appreciate their cultural heritage. Students showed an increase in appreciation for Indonesian literature as well as increased participation in cultural activities related to the preservation of local culture. Theoretically, the Full of Love Curriculum can be positioned as a variant of the culture-based humanistic curriculum that can strengthen national identity. Empirically, these findings confirm that learning Indonesian Literature based on compassion and rooted in local wisdom can be an effective strategy in fostering a love of culture and national identity among madrasah students.   Kurikulum Penuh Cinta dalam pembelajaran Sastra Indonesia bertujuan untuk memperkuat kecintaan siswa terhadap budaya dan identitas nasional melalui pendekatan humanistik yang memprioritaskan hubungan emosional yang hangat antara guru dan siswa. Penelitian ini bertujuan untuk mengeksplorasi implementasi kurikulum ini di MAN 1 Mandailing Natal dan dampaknya terhadap identitas budaya dan nasionalisme siswa. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus. Data dikumpulkan melalui observasi, wawancara mendalam dengan guru dan siswa, serta analisis dokumen yang berkaitan dengan kurikulum dan bahan ajar. Peneliti menganalisis dampak implementasi Kurikulum Penuh Cinta terhadap penguatan identitas budaya siswa dan kebanggaan mereka terhadap Indonesia. Hasil penelitian menunjukkan bahwa implementasi Kurikulum Penuh Cinta di MAN 1 Mandailing Natal efektif dalam menumbuhkan rasa bangga terhadap budaya Indonesia dan memperkuat identitas nasional siswa. Pembelajaran sastra yang mengintegrasikan nilai-nilai budaya lokal Mandailing dan nasionalisme Indonesia mendorong siswa untuk lebih memahami dan menghargai warisan budaya mereka. Siswa menunjukkan peningkatan apresiasi terhadap sastra Indonesia serta peningkatan partisipasi dalam kegiatan budaya yang berkaitan dengan pelestarian budaya lokal. Secara teoritis, Kurikulum Penuh Cinta dapat diposisikan sebagai varian dari kurikulum humanistik berbasis budaya yang dapat memperkuat identitas nasional. Secara empiris, temuan ini menegaskan bahwa pembelajaran Sastra Indonesia yang berlandaskan kasih sayang dan berakar pada kearifan lokal dapat menjadi strategi yang efektif dalam menumbuhkan kecintaan terhadap budaya dan identitas nasional di kalangan siswa madrasah.